Mechanisms and Clinical Consequences of Vascular Calcification - Zhu, Dongxing; Mackenzie, Neil C.; Farquharson, Colin; Macrae, Vicky E. (Frontiers in Endocrinology, 2012)
Vascular calcification has severe clinical consequences and is considered an accurate predictor of future adverse cardiovascular events, including myocardial infarction and stroke. Previously vascular calcification was thought to be a passive process which involved the deposition of calcium and phosphate in arteries and cardiac valves. However, recent studies have shown that vascular calcification is a highly regulated, cell-mediated process similar to bone formation. In this article, we outline the current understanding of key mechanisms governing vascular calcification and highlight the clinical consequences. By understanding better the molecular pathways and genetic circuitry responsible for the pathological mineralization process novel drug targets may be identified and exploited to combat and reduce the detrimental effects of vascular calcification on human health.